EDUKASI TERSTRUKTUR SEBAGAI UPAYA PENGUATAN SIKAP WARGA DESA UNTUK MENCEGAH PENULARAN COVID-19 MELALUI CLUSTER KELUARGA - Eny Sendra; Tanto Hariyanto; Arika Indah Setyarini (Politeknik Kesehatan Kemenkes malang, 2021)
The emergence of new Covid-19 cluster, namely the family cluster, has raised concerns in the community. The family cluster spread the corona virus originating from family members or people who live in the same house. Usually, the spread begins with someone who has been infected first and then spreads it to other family members. Good knowledge provides a correlation of potential attitudes towards efforts to prevent disease transmission, and vice versa. Providing education is an effective way to increase knowledge about efforts to prevent Covid-19 transmission. Community service is held by providing virtual counseling with zoom meeting media. Participants consisted of villagers and cadres. The results of the pre-test and post-test showed a change in the tendency to be positive in efforts to prevent the transmission of Covid-19 infection through family clusters which can be seen from an increase in the number of answers that showed a positive attitude on the post test compared to the pre test. Motivation and correct information related to efforts to prevent Covid-19 transmission through family clusters are needed, not just one activity, but must be repeated and continuous.